GAMBARAN PENGETAHUAN TENTANG PENCEGAHAN HIV/AIDS PADA REMAJA DI SMK AL-HURRIYYAH KARAWANG TAHUN 2011 - Nursolihah, Iha; Suryani, Rotua (Jurnal Kesehatan AYURVEDA, 2012)
Background: PP and PL kemenkes directorate RI reported cumulative cases HIV/AIDS in Indonesia since it was first discovered in 1987 until31 December 2012 amounted to 98.390 cases and 45.499 cases of HIV/AIDS, with new cases in 2012 as many as 21.511 people HIV, AIDS 5.686 man and 1.146 people died. West Java was ranked 4th out of 33 provinces in Indonesia by number of cases of HIV and AIDS as many as 7.157 cases of 4.098. The prevalence of HIV/AIDS in Karawang, West Java increased sharply, AIDS Prevention Commission Report (KPA) Karawang the patients of HIV/AIDS as many as 283 people from the age of 15-30 years. Objective: To know the characteristics of respondents by sex and age, as well as reveal the respondents knowledge about the prevention of HIV/AIDS. Methods:Research conducted was descriptive research that is done in SMK AL-Hurriyyah Karawang with 54 samples. Results:The characteristics showed that most respondents by sex as much as 37 respondents were women(68.5%) and by the age of 16-18 years of age were 53 respondents (98.1%). While the respondents knowledgeabout the prevention of HIV/AIDS the most categories is the less category as many as 47 respondents (87%) and category ample much as 7 respondents (13%). Conclusion:Knowledge about the prevention of HIV/AIDS among adolescents in SMK Al-Hurriyyah in less category.Keywords: Knowledge, Youth SMK Al-Hurriyyah, Prevention of HIV/AIDS.